DAMPAK PEMURIDAN BAGI PEMBENTUKAN KARAKTER ANAK-ANAK REMAJA USIA 12-17 TAHUN DI JUNIOR CHURCH GEREJA BETHEL INDONESIA TABGHA BATAM CENTRE - Steven Lin; Junita elfrida Hutahaean (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2023)
The problem currently being faced is the decline in the character of the teenagers in the junior church. We are aware that currently most of the teenagers are experiencing character crisis problems, they are not controlled by the influence of the development of this era. Therefore, the role of the church is very much needed in controlling the existing character problems. Therefore, it is very important for teenagers to be discipled so that they have the character of Christ which has an impact on social life. Seeing the existing problems, the purpose of this study is to describe discipleship as an effort to build character for young people in the Junior Church. The method used in this research is qualitative. Collecting data through observation and interviews. All participants can understand and participate in the discipleship process that takes place by giving life examples by followers of Christ. From the results of the study, it was found that discipleship carried out at the Junior Church has an impact on shaping the character of young people so that they have values and characters that reflect Christ in them.